2018
DOI: 10.1093/mnras/sty2791
|View full text |Cite
|
Sign up to set email alerts
|

Thorium in solar twins: implications for habitability in rocky planets

Abstract: We have investigated the thorium (Th) abundance in a sample of 53 thin disc solar twins covering a wide range of ages. These data provide constrains on the mantle energy budget of terrestrial planets that can be formed over the evolution of the Galaxy's thin disc. We have estimated Th abundances with an average precision of 0.025 dex (in both [Th/H] and [Th/Fe]) through comprehensive spectral synthesis of a Th II line present at 4019.1290Å, using very high resolution (R = 115,000) high quality HARPS spectra ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…The sample is composed of 67 solar twins, stars with atmospheric parameters very similar to the Sun, within around ±100 K in T eff and ±0.1 dex in log g and [Fe/H] (Ramírez, Meléndez & Asplund 2009), studied previously by Bedell et al (2018), Spina et al (2018), and Botelho et al (2019. The atmospheric parameters are those by Spina et al (2018).…”
Section: S O L a R T W I N S S A M P L E A N D Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The sample is composed of 67 solar twins, stars with atmospheric parameters very similar to the Sun, within around ±100 K in T eff and ±0.1 dex in log g and [Fe/H] (Ramírez, Meléndez & Asplund 2009), studied previously by Bedell et al (2018), Spina et al (2018), and Botelho et al (2019. The atmospheric parameters are those by Spina et al (2018).…”
Section: S O L a R T W I N S S A M P L E A N D Datamentioning
confidence: 99%
“…In the current work we have homogeneously measured precise abundances of carbon and nitrogen plus the carbon main isotopic ratio 12 C/ 13 C, in a sample of well-studied solar twins, having distances up to 100 pc and spanning a wide range of ages since around the formation epoch of the Galaxy's thin disc until a few hundreds Myr ago (Bedell et al 2018;Spina et al 2018;Botelho et al 2019). The analysis of our results is focused on the distributions of a set of CNO abundance ratios as a function of the age and metallicity of these solar twins in order to provide unprecedented and self-consistent constraints for GCE modelling (e.g.…”
mentioning
confidence: 99%
“…Spectroscopic surveys of solar twins and analogs have shown that the solar abundance of thorium is a few times lower (< 3) than other stars in the sample (Unterborn et al 2015;Botelho et al 2019). Overall, some worlds will be characterized by elevated abundances of long-lived radionuclides (Lugaro et al 2018).…”
Section: Biological Implicationsmentioning
confidence: 99%
“…Bulk composition and mantle mineralogy affect the transport and material properties of the mantle, such as density and viscosity (Takeda 1998;Yamazaki & Karato 2001), and melting behavior (Hirschmann 2000;Kiefer et al 2015). Additionally, the budget of radiogenic elements varies among stars (Frank et al 2014;Unterborn et al 2015;Botelho et al 2019) and determines the heat production in planetary mantles, which also moderates the style of interior convection.…”
Section: Introductionmentioning
confidence: 99%